A fuel cell catalyst, its preparation method and use
Patent Information
- Application Number
- CN202310875698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-17
AI Technical Summary
[0003]离聚物的添加虽然可以提高催化层的质子导率,但是也会带来催化剂活性位点覆盖,氧气传质阻力增加,磺酸基团与Pt催化活性位点接触毒化等问题
[0044](1)本发明所述燃料电池催化剂的催化活性与传统的Pt/C催化剂相近,应用于燃料电池时的质子传导率与添加离聚物的Pt/C催化剂相近,故本发明所述燃料电池催化剂在用于燃料电池时,无须在燃料电池中添加离聚物,可以避免传统催化层中使用离聚物造成的Pt活性位点过度覆盖造成的氧气传质阻力增大问题。
Smart Images

Figure CN116799232B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cell technology, and relates to a fuel cell catalyst, its preparation method, and its application. Background Technology
[0002] Platinum-carbon catalysts are a key component of the catalyst layer in proton exchange membrane fuel cells, catalyzing the oxygen reduction reaction. However, platinum-carbon catalysts exhibit poor proton conductivity within the catalyst layer, necessitating the addition of ionomers to improve proton conductivity, thereby accelerating proton conduction and enhancing fuel cell performance.
[0003] While the addition of ionomers can improve the proton conductivity of the catalyst layer, it can also lead to problems such as catalyst active site coverage, increased oxygen mass transfer resistance, and poisoning of Pt catalytic active sites by sulfonic acid groups.
[0004] CN113594475A discloses a fuel cell catalyst layer and its preparation method. The shielding gases used, such as CO, sulfides, and nitrides, are highly susceptible to adsorption and combination with platinum, causing poisoning of platinum active sites. Subsequent voltage cycling methods are unable to completely remove the adsorbed shielding gases, resulting in a decrease in catalyst activity. In addition, the adsorption of shielding gases onto the surface of platinum active particles does not prevent the formation of a thicker ionomer film structure. Oxygen still needs to pass through the conductive catalyst surface of the thicker ionomer film, which cannot effectively solve the problem of high oxygen mass transfer resistance.
[0005] CN109103472A discloses a high oxygen transport fuel cell catalyst layer and membrane electrode assembly, and a fuel cell. However, the uniformity of the mixing of the cationic polymer and ionomer in this method is uncontrollable, making it difficult to reduce the overall density of the ionomer membrane in the catalyst layer through the steric hindrance effect generated by their electrostatic interaction. Furthermore, the cationic polymer added by this method is inherently unstable and lacks oxygen reduction activity, which can generate free ions that degrade fuel cell performance or even poison the catalyst active sites.
[0006] The catalysts used in the above schemes have problems such as low proton conductivity and poisoning of active sites, which limits their practical application. Summary of the Invention
[0007] The purpose of this invention is to provide a fuel cell catalyst, its preparation method, and its application. The fuel cell catalyst of this invention has excellent proton conductivity while ensuring catalytic activity, avoiding the addition of ionomers in the fuel cell and reducing the oxygen conduction resistance of the fuel cell.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a fuel cell catalyst, the fuel cell catalyst comprising a hydrogenated composite metal oxide framework and a metal active component M supported on the surface of the hydrogenated composite metal oxide framework, wherein the chemical formula of the hydrogenated composite metal oxide framework is A. x B y O m H n Wherein, A includes alkaline earth metals and / or rare earth metals, B includes transition metals, x is 1 to 5, y is 1 to 7, m is 1 to 5, and n is 1 to 3.
[0010] This invention uses a hydrogenated composite metal oxide framework as a carrier to support metal active components. The fuel cell catalyst has a high proton conductivity. When applied to fuel cells, there is no need to add ionomers, which avoids the problem of increased oxygen mass transfer resistance caused by excessive coverage of metal active components in traditional catalyst layers. The hydrogenated composite metal oxide framework of this invention does not contain sulfonic acid groups, thus solving the problem of sulfonic acid groups contacting metal active components in traditional ionomers, poisoning catalytic active sites, and causing catalyst deactivation.
[0011] Preferably, the active metal component M includes any one or a combination of at least two of the following: Pt, Ru, Ir, Pt-transition metal complex, Ru-transition metal complex, or Ir-transition metal complex.
[0012] The metal active component used in the fuel cell catalyst of the present invention can be a noble metal or a complex of a transition metal (e.g., Co, Ni, or Fe) and a noble metal. Using a transition metal to replace part of the noble metal as the active component provides a similar catalytic effect to the noble metal, but at a significantly lower cost, making it more suitable for practical applications.
[0013] Preferably, the alkaline earth metal includes any one or a combination of at least two of Be, Mg, Ca, Sr or Ba.
[0014] Preferably, the rare earth metal includes any one or a combination of at least two of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, or Yb.
[0015] Preferably, the transition metal includes any one or a combination of at least two of Co, Cr, Fe, Mn, Ni, Cu, Ti, Zn, Sc, or V.
[0016] Preferably, the morphology of the hydrogenated composite metal oxide framework includes nanosheets.
[0017] Preferably, the mass ratio of the active metal component to the hydrogenated composite metal oxide skeleton is (0.2 to 0.7):1, for example: 0.2:1, 0.3:1, 0.4:1, 0.5:1 or 0.7:1, etc.
[0018] In a second aspect, the present invention provides a method for preparing a fuel cell catalyst as described in the first aspect, the method comprising the following steps:
[0019] (1) Soluble salt A and soluble salt B are mixed with an organic solvent, and the pH is adjusted to carry out a one-step microwave heating reaction, which is then pyrolyzed to obtain a composite metal oxide.
[0020] (2) Mix soluble M salt, organic solvent and composite metal oxide, adjust pH and carry out a two-step microwave heating reaction to obtain composite material;
[0021] (3) The composite material is subjected to hydrogen intercalation treatment under an external electric field to obtain the fuel cell catalyst.
[0022] Preferably, the organic solvent in step (1) includes ethylene glycol.
[0023] Preferably, the pH in step (1) is 11.5 to 12.5, for example: 11.5, 11.8, 12, 12.2 or 12.5, etc.
[0024] Preferably, the temperature of the microwave heating reaction in step (1) is 100-120°C, for example: 100°C, 105°C, 110°C, 115°C or 120°C.
[0025] Preferably, the microwave heating reaction time in step (1) is 20 to 40 minutes, for example: 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes.
[0026] Preferably, the step (1) involves microwave heating followed by filtration.
[0027] Preferably, the atmosphere for pyrolysis in step (1) includes oxygen.
[0028] Preferably, the pyrolysis temperature in step (1) is 200 to 800°C, for example: 200°C, 300°C, 500°C, 600°C or 800°C.
[0029] Preferably, the pyrolysis time in step (1) is 1 to 6 hours, for example: 1 hour, 2 hours, 3 hours, 4 hours or 6 hours.
[0030] Preferably, the organic solvent in step (2) includes any one or a combination of at least two of ethylene glycol, ethanol, or isopropanol.
[0031] Preferably, the pH in step (2) is 11.5 to 12.5, for example: 11.5, 11.8, 12, 12.2 or 12.5, etc.
[0032] Preferably, the temperature of the two-step microwave heating reaction in step (2) is 100-200℃, for example: 100℃, 120℃, 150℃, 180℃ or 200℃.
[0033] Preferably, the two-step microwave heating reaction in step (2) takes 1.5 to 2.5 hours, for example: 1.5 hours, 1.8 hours, 2 hours, 2.2 hours or 2.5 hours.
[0034] Preferably, the hydrogen intercalation treatment under an applied electric field in step (3) includes:
[0035] The composite material is loaded onto the surface of a conductive glass to obtain a first electrode. The first electrode and the second electrode are then immersed in an ionic liquid with a gap between them and connected to a DC power supply. The first electrode is connected to the negative electrode and the second electrode is connected to the positive electrode. After the reaction is carried out by electricity, the fuel cell catalyst is obtained.
[0036] This invention increases the proton conductivity of the catalyst by applying an external electric field for hydrogen intercalation treatment, and avoids the poisoning of the catalyst active sites by the presence of sulfonic acid groups.
[0037] Preferably, the loading method includes any one or a combination of at least two of impregnation, spraying, or coating.
[0038] Preferably, the ionic liquid contains hydrogen ions and oxygen ions.
[0039] Preferably, the ionic liquid includes a DEME-TFSI type ionic liquid.
[0040] Preferably, the second electrode comprises any one or a combination of at least two of the following: a parallel plate electrode, a rod electrode, or a metal mesh electrode.
[0041] Preferably, the current applied is 2 to 3A, for example: 2A, 2.2A, 2.5A, 2.8A or 3A, etc.
[0042] Thirdly, the present invention provides a fuel cell comprising the fuel cell catalyst as described in the first aspect.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The catalytic activity of the fuel cell catalyst described in this invention is similar to that of the traditional Pt / C catalyst. When applied to fuel cells, the proton conductivity is similar to that of the Pt / C catalyst with added ionomers. Therefore, when the fuel cell catalyst described in this invention is used in fuel cells, there is no need to add ionomers to the fuel cell. This can avoid the problem of increased oxygen mass transfer resistance caused by excessive coverage of Pt active sites due to the use of ionomers in the traditional catalyst layer.
[0045] (2) The fuel cell catalyst of the present invention does not contain sulfonic acid groups, which solves the problem of catalyst deactivation caused by the contact between sulfonic acid groups and metal active components in traditional ionomers, which poisons the catalytic active sites.
[0046] (3) The fuel cell catalyst described in this invention benefits from its high proton conductivity, resulting in a single-cell performance of 1 A / cm. 2 The voltage can reach above 0.728V at current density, which is better than the traditional Pt / C catalyst at 0.715V, showing good application prospects. Attached Figure Description
[0047] Figure 1 This is a SEM image of the fuel cell catalyst described in Example 1 of the present invention.
[0048] Figure 2 This is a TEM image of the fuel cell catalyst described in Example 1 of the present invention.
[0049] Figure 3 This is a TEM magnified image of the fuel cell catalyst described in Example 1 of the present invention.
[0050] Figure 4 This is an impedance comparison diagram of the fuel cell catalyst described in Example 1 of the present invention and the fuel cell catalyst described in Comparative Example 1.
[0051] Figure 5 This is a comparison diagram of the polarization performance of the fuel cell catalyst described in Example 1 of the present invention and the fuel cell catalyst described in Comparative Example 1.
[0052] Figure 6 This is a comparison graph of the polarization curves of the fuel cell catalysts described in Examples 1-5 and Comparative Examples 1-2. Detailed Implementation
[0053] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0054] Example 1
[0055] This embodiment provides a fuel cell catalyst, and the preparation method of the fuel cell catalyst is as follows:
[0056] (1) Strontium chloride and cobalt chloride were mixed with ethylene glycol in a molar ratio of 1:1. Sodium hydroxide was added to adjust the pH to 12. The mixture was then microwave-heated at 110°C for 30 min under a nitrogen atmosphere. Finally, it was placed in a tube furnace and pyrolyzed at 400°C for 2 h under an oxygen atmosphere to obtain a composite metal oxide.
[0057] (2) After mixing chloroplatinic acid and ethylene glycol, add composite metal oxide, stir evenly, adjust the pH of the solution to 12, and then microwave heat the reaction at 150°C for 2 hours under nitrogen atmosphere to obtain composite material.
[0058] (3) The composite material is loaded onto the surface of a conductive glass to obtain the first electrode. The first electrode and the parallel plate electrode are immersed alternately in a DEME-TFSI type ionic liquid and connected to a DC power supply. The first electrode is connected to the negative electrode and the second electrode is connected to the positive electrode. A 3A current is applied to obtain the fuel cell catalyst. The chemical formula of the catalyst is Pt@SrCoO3H, and the active component Pt is loaded at 50% in the catalyst.
[0059] The SEM image of the fuel cell catalyst is shown below. Figure 1 As shown, by Figure 1 As can be seen, the fuel cell catalyst of the present invention is composed of nanosheets arranged in a three-dimensional petal-like structure.
[0060] The TEM image of the fuel cell catalyst is shown below. Figure 2-3 As shown, by Figure 2-3 As can be seen, in the fuel cell catalyst of the present invention, the Pt nanoparticles have a particle size of about 3-5 nm and are uniformly loaded on the surface of SrCoO3H nanosheets.
[0061] Example 2
[0062] This embodiment provides a fuel cell catalyst, and the preparation method of the fuel cell catalyst is as follows:
[0063] (1) Strontium nitrate and cobalt nitrate were mixed with ethylene glycol at a molar ratio of 1:1. Sodium hydroxide was added to adjust the pH to 11.5. The mixture was then microwave-heated at 120°C for 20 min under a nitrogen atmosphere. The mixture was then placed in a tube furnace and pyrolyzed at 200°C for 6 h under an oxygen atmosphere to obtain a composite metal oxide.
[0064] (2) After mixing platinum acetylacetonate with ethylene glycol, the composite metal oxide was added, stirred evenly, and the pH of the solution was adjusted to 12. The reaction was carried out under a nitrogen atmosphere and microwave heating at 100°C for 2.5 h to obtain the composite material.
[0065] (3) The composite material is loaded onto the surface of a conductive glass to obtain a first electrode. The first electrode and a parallel plate electrode are immersed alternately in a DEME-TFSI type ionic liquid and connected to a DC power supply. The first electrode is connected to the negative electrode, and the second electrode is connected to the positive electrode. A 2A current is applied to obtain the fuel cell catalyst. The chemical formula of the catalyst is Pt@SrCoO2H, and the loading of the active component Pt in the catalyst is 40%.
[0066] Example 3
[0067] This embodiment provides a fuel cell catalyst, and the preparation method of the fuel cell catalyst is as follows:
[0068] (1) Cerium chloride and ferric nitrate were mixed with ethylene glycol in a molar ratio of 1:1. Sodium hydroxide was added to adjust the pH to 12.5. The mixture was then microwave-heated at 130°C for 1 hour under a nitrogen atmosphere. The mixture was then placed in a tube furnace and pyrolyzed at 800°C for 1 hour under an oxygen atmosphere to obtain a composite metal oxide.
[0069] (2) After mixing chloroplatinic acid and ethylene glycol, add the composite metal oxide, stir evenly, adjust the pH of the solution to 12, and then microwave heat the reaction at 200°C for 1.5 h under nitrogen atmosphere to obtain the composite material.
[0070] (3) The composite material is loaded onto the surface of a conductive glass to obtain a first electrode. The first electrode and a parallel plate electrode are immersed alternately in a DEME-TFSI type ionic liquid and connected to a DC power supply. The first electrode is connected to the negative electrode, and the second electrode is connected to the positive electrode. A 2A current is applied to obtain the fuel cell catalyst. The chemical formula of the catalyst is Pt@CeFeO5H2, and the loading of the active component Pt in the catalyst is 60%.
[0071] Example 4
[0072] The only difference between this embodiment and embodiment 1 is that the current applied in step (2) is 1A, while the other conditions and parameters are exactly the same as in embodiment 1.
[0073] Example 5
[0074] The only difference between this embodiment and embodiment 1 is that the current applied in step (2) is 5A, while the other conditions and parameters are exactly the same as in embodiment 1.
[0075] Comparative Example 1
[0076] This comparative example uses a Pt / C catalyst with a platinum content of 60%.
[0077] Comparative Example 2
[0078] The only difference between this comparative example and Example 1 is that step (3) is omitted; all other conditions and parameters are exactly the same as in Example 1.
[0079] Performance testing:
[0080] The catalysts prepared in the examples and comparative examples were tested. Proton conductivity testing details are provided in Part 5 of GB / T 20042.3-2009, and catalytic activity testing details are provided in Section 10.5 of GB / T 20042.4-2009, Polarization Curve Testing. The test results are shown in Table 1. Figure 6 As shown:
[0081] Table 1
[0082] Example 1 0.13 0.734 Example 2 0.12 0.731 Example 3 0.12 0.728 Example 4 0.09 0.718 Example 5 0.10 0.721 Comparative Example 1 0.05 0.715 Comparative Example 2 0.06 0.714
[0083] As shown in Table 1, and based on Examples 1-3, the proton conductivity of the fuel cell catalyst described in this invention can reach above 0.12 S / cm, and the catalytic activity can reach 0.728 @ 1 A / cm. 2 above.
[0084] Comparing Examples 1 and 4-5, it can be seen that in the preparation process of the fuel cell catalyst of the present invention, the current of the H intercalation treatment in step (3) will affect the performance of the prepared catalyst. The catalyst performance is better when the current is controlled at 2-3A. If the current is too large, it will cause excessive oxidation and corrosion of the material, resulting in the destruction of the material's own structure. If the current is too small, it is difficult to effectively realize the H intercalation process, and the proton conductivity is low.
[0085] As can be seen from the comparison between Example 1 and Comparative Example 1, the fuel cell catalyst of the present invention, while ensuring the catalytic activity of the catalyst, solves the problem of poor proton conductivity of traditional platinum-carbon catalysts, reduces or even avoids the use of ionomers, which is of great significance for reducing the cost of fuel cells.
[0086] As can be seen from the comparison between Example 1 and Comparative Example 2, the present invention can increase the proton conductivity of the catalyst by applying an external electric field for hydrogen intercalation treatment, and avoid the poisoning of the catalyst active sites by the presence of sulfonic acid groups.
[0087] The catalyst prepared in Example 1 was used to fabricate a membrane electrode without ionomers, and its single-cell performance was compared with that of a traditional platinum-carbon membrane electrode containing ionomers.
[0088] First, the membrane electrode was prepared using the following slurry formulation: A certain amount of Pt@SrCoO2H1 and the Pt / C catalyst from Comparative Example 1 were dispersed in a mixed solution of isopropanol and water, with an alcohol-to-water ratio of 15:1 and a solid content of 0.01%. Then, an ionomer was added to the Pt / C catalyst slurry to achieve an I / C ratio of 0.75. Both were then ultrasonically pulverized for 40 minutes in a cell ultrasonic pulverizer before use. The uniformly mixed catalyst slurry was then sprayed onto the surface of the proton exchange membrane using an ultrasonic sprayer, corresponding to a Pt loading of 0.462 mg / cm³. 2 0.465 mg / cm 2 Subsequently, its impedance was analyzed, and the results are as follows: Figure 4 As shown, from Figure 4 The results show that the impedance of the Pt@SrCoO2H1 membrane electrode without ionomers did not increase significantly compared to the Pt / C membrane electrode with traditional ionomers, proving that the impedance of Pt@SrCoO2H1 membrane electrode without ionomers did not increase significantly compared to the Pt / C membrane electrode with traditional ionomers. x H y The catalyst has proton conductivity comparable to that of traditional ionomers.
[0089] Single-cell polarization performance analysis was performed on the Pt@SrCoO2H1 catalyst and the Pt / C catalyst of Comparative Example 1. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen from the data that the fuel cell prepared by Pt@SrCoO2H1 without the addition of ionomers achieves a speed of 1 A / cm. 2 At the same current density, its voltage can reach 0.734V, while under the same conditions, the film electrode sample using traditional ionomers only reaches 1A / cm. 2 At current density, its voltage is only 0.715V. The fuel cell prepared by Pt@SrCoO2H1 without adding ionomers has significantly improved polarization performance compared with the fuel cell prepared by traditional Pt / C catalyst with added ionomers. This further proves that the fuel cell catalyst of the present invention can effectively carry out proton conduction and solves the problems of catalyst poisoning and increased oxygen mass transfer resistance caused by traditional ionomers covering the catalyst surface.
[0090] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A fuel cell catalyst, characterized in that, The fuel cell catalyst comprises a hydrogenated composite metal oxide framework and a metal active component M supported on the surface of the hydrogenated composite metal oxide framework, wherein the chemical formula of the hydrogenated composite metal oxide framework is A. x B y O m H n Where A includes alkaline earth metals and / or rare earth metals, B includes transition metals, x is 1~5, y is 1~7, m is 1~5, and n is 1~3; The fuel cell catalyst is prepared by the following method: (1) Mix soluble salt A and soluble salt B with an organic solvent, adjust the pH and carry out a one-step microwave heating reaction, and pyrolyze to obtain composite metal oxide; (2) Mix soluble M salt, organic solvent and composite metal oxide, adjust pH and carry out a two-step microwave heating reaction to obtain composite material; (3) The composite material is subjected to hydrogen intercalation treatment under an external electric field to obtain the fuel cell catalyst; The applied electric field hydrogen intercalation treatment includes: The composite material is loaded onto the surface of a conductive glass to obtain a first electrode. The first electrode and the second electrode are then immersed in an ionic liquid with a gap between them and connected to a DC power supply. The first electrode is connected to the negative electrode and the second electrode is connected to the positive electrode. After the reaction is carried out by electricity, the fuel cell catalyst is obtained.
2. The fuel cell catalyst according to claim 1, characterized in that, The active metal component M includes any one or a combination of at least two of the following: Pt, Ru, Ir, Pt-transition metal complex, Ru-transition metal complex, or Ir-transition metal complex.
3. The fuel cell catalyst according to claim 1, characterized in that, The alkaline earth metals include any one or a combination of at least two of Be, Mg, Ca, Sr, or Ba.
4. The fuel cell catalyst according to claim 1, characterized in that, The rare earth metals include any one or a combination of at least two of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, or Yb.
5. The fuel cell catalyst according to claim 1, characterized in that, The transition metal includes any one or a combination of at least two of Co, Cr, Fe, Mn, Ni, Cu, Ti, Zn, Sc, or V.
6. The fuel cell catalyst according to claim 1, characterized in that, The morphology of the hydrogenated composite metal oxide framework includes nanosheets.
7. The fuel cell catalyst according to claim 1, characterized in that, The mass ratio of the active metal component to the hydrogenated composite metal oxide framework is (0.2~0.7):
1.
8. A method for preparing a fuel cell catalyst as described in any one of claims 1-7, characterized in that, The preparation method includes the following steps: (1) Mix soluble salt A and soluble salt B with an organic solvent, adjust the pH and carry out a one-step microwave heating reaction, and pyrolyze to obtain composite metal oxide; (2) Mix soluble M salt, organic solvent and composite metal oxide, adjust pH and carry out a two-step microwave heating reaction to obtain composite material; (3) The composite material is subjected to hydrogen intercalation treatment under an external electric field to obtain the fuel cell catalyst; The applied electric field hydrogen intercalation treatment includes: The composite material is loaded onto the surface of a conductive glass to obtain a first electrode. The first electrode and the second electrode are then immersed in an ionic liquid with a gap between them and connected to a DC power supply. The first electrode is connected to the negative electrode and the second electrode is connected to the positive electrode. After the reaction is carried out by electricity, the fuel cell catalyst is obtained.
9. The preparation method according to claim 8, characterized in that, The organic solvent in step (1) includes ethylene glycol.
10. The preparation method according to claim 8, characterized in that, The pH in step (1) is 11.5~12.
5.
11. The preparation method according to claim 8, characterized in that, The temperature of the microwave heating reaction in step (1) is 100~120℃.
12. The preparation method according to claim 8, characterized in that, The microwave heating reaction time in step (1) is 20~40 min.
13. The preparation method according to claim 8, characterized in that, Step (1) involves a microwave heating reaction followed by filtration.
14. The preparation method according to claim 8, characterized in that, The atmosphere for pyrolysis in step (1) includes oxygen.
15. The preparation method according to claim 8, characterized in that, The pyrolysis temperature in step (1) is 200~800℃.
16. The preparation method according to claim 8, characterized in that, The pyrolysis time in step (1) is 1 to 6 hours.
17. The preparation method according to claim 8, characterized in that, The organic solvent in step (2) includes any one or a combination of at least two of ethylene glycol, ethanol or isopropanol.
18. The preparation method according to claim 8, characterized in that, The pH in step (2) is 11.5~12.
5.
19. The preparation method according to claim 8, characterized in that, The temperature of the two-step microwave heating reaction in step (2) is 100~200℃.
20. The preparation method according to claim 8, characterized in that, The time for the two-step microwave heating reaction in step (2) is 1.5~2.5h.
21. The preparation method according to claim 8, characterized in that, The loading method includes any one or a combination of at least two of the following: impregnation, spraying, or coating.
22. The preparation method according to claim 8, characterized in that, The ionic liquid contains hydrogen ions and oxygen ions.
23. The preparation method according to claim 8, characterized in that, The ionic liquid includes DEME-TFSI type ionic liquid.
24. The preparation method according to claim 8, characterized in that, The second electrode includes any one or a combination of at least two of the following: a parallel plate electrode, a rod electrode, or a metal mesh electrode.
25. The preparation method according to claim 8, characterized in that, The current supplied is 2~3A.
26. A fuel cell, characterized in that, The fuel cell comprises a fuel cell catalyst as described in any one of claims 1-7.
Citation Information
Patent Citations
A high oxygen transport fuel cell catalytic layer and a membrane electrode assembly and a fuel cell
CN109103472A
Fuel cell catalyst layer and preparation method thereof
CN113594475A
Single part used for fuel cell and preparation method for single part
CN106981675A
Cathode catalyst layer for high-temperature proton exchange membrane fuel cell as well as preparation method and application of cathode catalyst layer
CN115312787A